Hubungan Pengetahuan Personal Hygiene Ibu Dengan Kejadian Diare Pada Balita Di Wilayah Kerja Puskesmas Jembatan Kecil Kota Bengkulu Tahun 2026 - Aulia Rahma Ningtyas; Meri Epriana Susanti; Delta Aprianti (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Globally, diarrhea is one of the leading causes of child mortality with approximately 1.7 billion cases annually and hundreds of thousands of deaths in infants (World Health Organization [WHO], 2024). In Bengkulu City, cases of diarrhea in toddlers showed an increase in 2024, with the Jembatan Kecil Community Health Center recording the highest number of cases (Bengkulu City Health Office, 2024). Lack of maternal knowledge about personal hygiene is one of the risk factors for diarrhea in toddlers (Indrayani, 2022). This study aims to determine the relationship between maternal personal hygiene knowledge and the incidence of diarrhea in toddlers in the Jembatan Kecil Community Health Center Work Area of Bengkulu City in 2026. The research method used was analytical with a cross-sectional design. The population in this study were mothers who have toddlers in the Jembatan Kecil Community Health Center Work Area. A sample of 67 respondents was taken using a purposive sampling technique with Chi-Square test analysis. The results showed that almost half of the respondents had good knowledge (38.8%) and the majority of respondents did not experience diarrhea (58.2%). There was a significant correlation between mothers' personal hygiene knowledge and the incidence of diarrhea in toddlers (p-value = 0.000). It is recommended that community health centers improve personal hygiene education for mothers of toddlers, educational institutions utilize it as an academic reference, and mothers improve hygiene practices to prevent diarrhea in toddlers.